Kemampuan Berpikir Komputasional di Sekolah Dasar Kelas 4 Pembelajaran Matematika - Muhammad Arvi; Chandra Chandra; Salmaini Safitri Syam (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The purpose of this study is to assess the computational thinking skills of fourth-grade elementary students within the framework of mathematics instruction. Computational thinking is a crucial 21st-century competency that should be cultivated from an early age, particularly in solving mathematical problems. This study adopts a descriptive quantitative method using a written test instrument developed based on four key computational thinking components: decomposition, pattern recognition, abstraction, and algorithmic processes. The participants in this research were fourth-grade students from a selected elementary school. The results indicate that most students demonstrate a moderate level of computational thinking. Among the assessed indicators, decomposition was the most successfully achieved, while algorithmic thinking was the least mastered. These results highlight the importance of integrating contextual and problem-based learning strategies to further enhance students’ computational thinking abilities in mathematics education.